2015
DOI: 10.1002/pi.4985
|View full text |Cite
|
Sign up to set email alerts
|

Reverse iodine transfer polymerization of vinyl acetate and vinyl benzoate: synthesis and characterization of homo- and copolymers

Abstract: Homo-and copolymers of vinyl esters including vinyl acetate (VAc) and vinyl benzoate (VBz) were synthesized via the reverse iodine transfer radical polymerization technique. Polymerization was carried out in the presence of iodine as the in situ generator of the transfer agent and 2,2 ′ -azobis(isobutyronitrile) as the initiator at 70 ∘ C. Reverse iodine transfer radical homopolymerization of VAc and VBz led to conversions of 76 and 57%, number-average molecular weights of 8266 and 9814 g mol −1 and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Nevertheless, low conversion and an increase in M n were gained after sms ITP (Table 1), which can be attributed to inherent defects formed by ITP. As reported by Iovu et al 36 and Abdollahi et al, 37 PVAc with an iodine end group (PVAc-I) is very sensitive to humidity, which could accelerate the degradation of the terminal iodine end, as the side reaction shown in Fig. S3.…”
Section: Resultsmentioning
confidence: 77%
“…Nevertheless, low conversion and an increase in M n were gained after sms ITP (Table 1), which can be attributed to inherent defects formed by ITP. As reported by Iovu et al 36 and Abdollahi et al, 37 PVAc with an iodine end group (PVAc-I) is very sensitive to humidity, which could accelerate the degradation of the terminal iodine end, as the side reaction shown in Fig. S3.…”
Section: Resultsmentioning
confidence: 77%
“…Abdollahi et al reported that in a bulk system, poly(vinyl acetate) with an iodine end group (PVAc-I) was very sensitive to humidity. 19 As described in Scheme 1, a portion of the living chains having an iodide end group is inevitably degraded into aldehyde, hydroiodic acid (HI), and acetic acid due to the reaction with water at high temperature (Scheme 1(a)). The resulting side product, PVAc having an aldehyde end group, produces a double bond between the carbonyl group at α and β positions and acetic acid through an aldol reaction (Scheme 1(c)).…”
Section: Papermentioning
confidence: 99%
“…Although the synthesis of PVAc through RDRP has been achieved to meet the emerging demands, 17 the high reactivity of VAc (unconjugated monomer) radicals makes the polymerization more difficult to control than that of (meth)acrylates and styrene, which are conjugated monomers. Specifically, the highly active propagating radicals of VAc easily undergo combination termination, degradation, 18,19 and chain transfer to the methine or the methyl groups on the polymer. [20][21][22] Owing to this drawback, the most widely used RDRP method to polymerize VAc is reversible addition-fragmentation chain transfer (RAFT) polymerization, 23,24 which is tolerant toward unprotected functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal radical initiator is necessary to supply sufficient radical flux during the polymerization. Iodine DT can be used for polymerization of most of the monomers [37][38][39][40]. Iodide-mediated radical polymerization has successfully been used in the homogeneous or heterogeneous mediums [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Iodine DT can be used for polymerization of most of the monomers [37][38][39][40]. Iodide-mediated radical polymerization has successfully been used in the homogeneous or heterogeneous mediums [37][38][39][40][41][42]. These techniques (ITP and RITP) are performed under catalyst-free condition; resulting in easy purification of product [42].…”
Section: Introductionmentioning
confidence: 99%